Search for the lightest chargino at root s=130 and 136 GeV - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; et al. (1996)
A search for pair production of the lightest chargino at √s = 130.4 and 136.3 GeV has been carried out using the data sample corresponding to the 5.92 pb-1 recorded by the DELPHI detector during the high energy run of LEP in the last period of 1995. The theoretical reference model has been the Minimal Supersymmetric Standard Model with R-parity conservation. The three topologies expected for the decay of a pair of charginos, namely two acoplanar leptons plus missing energy (ℓℓ), two jets and an isolated lepton plus missing energy (jjℓ) and missing energy in a hadronic environment (√s), were investigated. No evidence of a signal was found. Lower mass limits were derived for various scenarios, including the case of a low mass difference between the chargino and the neutralino and of a light sneutrino. The mass limits range between 56.3 GeV/c2 and the kinematic limit.